Low Level of Circulating Activated Protein C Is a Risk Factor for Venous Thromboembolism - España, Francisco; Vayá, Amparo; Mira, Yolanda; Medina, Pilar; Estellés, Amparo; Villa, Piedad; Falcó, Cristina; Aznar, Justo (Thrombosis and Haemostasis, 2001)
The levels of circulating activated protein C (APC) reflect in vivo protein C activation. The aim of this study was to determine whether a low APC level is an independent risk factor for venous thromboembolism (VTE). We measured APC in 160 patients with a history of VTE and without recognized thrombophilic defects, and in 199 healthy individuals. The mean (±SD) APC level was lower in patients (0.99 ± 0.44 ng/ml) than in controls (1.19 ± 0.41 ng/ml) (p <0.0001), and showed a different distribution in the two groups. Thirty-eight patients (23.7%) had APC levels below the 5th percentile of the control group (<0.69 ng/ml) and 57 patients (35.6%) had APC levels below the 10th percentile (<0.77 ng/ml). APC levels <0.69 ng/ml increased the risk of a single or recurrent episode of VTE 4.2-fold (95% confidence interval, 2.0-9.0) or 6.9-fold (2.6-17.9), respectively, and APC levels <0.77 ng/ml increased these risks 3.4-fold (1.9-6.2) or 5.1-fold (2.3-11.2), respectively, compared with controls. Familial studies revealed that in some cases the low APC phenotype seems to be hereditary. We conclude that a low level of circulating APC in individuals without any of the most recognized thrombophilic defects is a prevalent, independent risk factor for VTE, and that it predisposes to recurrent VTE.
Keywords: Thromboembolism; protein C; activated protein C; venous thrombosis; risk factor